Composição e riqueza da ictiofauna do rio Apodi/Mossoró, semiárido do Rio Grande do Norte - Santos, Geferson Mario Rebouças dos (Universidade Federal Rural do Semi-Árido, 2017)
Apodi/Mossoró river hydrographic basin has an area of 14,276 km², reaching its highest tide at 469,714,600 m³ of water in its 618 registered dams. The Apodi/Mossoró river, the main river of the basin, is 210 km long, rising in the western part of the state, in the city of Luís Gomes and its mouth in the Atlantic Ocean between the municipalities of Areia Branca and Grossos. Facing the need of being aware of the freshwater ictiofauna, the objective was to survey the composition and variaty of fish species present in the Apodi/Mossoró river. The collections were carried out semiannually between 2013, 2015 and 2016 covering the rainy and dry seasons. At the end of each season, being June for the rainy season and December for the drought, samples were collected, with sampling in sixteen distinct regions of the river, with different habitat characteristics, covering the upper, middle and lower regions of the basin, until the entrance of the river in the estuary. The fish were sampled by means of trawls (05 m wide and 1,60 high, with a mesh of 05 mm), a tarrafa (50 and 70 mm mesh) and a picaré (1,40 x 0,90 m, with 1 mm mesh) in a sample period of 1 hour for each point.The captured specimens were packed in plastic bags and the laboratory from the Ufersa were screened and identified to the lowest taxonomic level. A total of 24,775 were collected, belonging to 08 orders, 19 families, 33 genres and 37 species. The order Characiformes was the most representative in relation to the number of species followed by the order Perciformes. The Characidae family was the most diversified followed by the Cichlidae family. Three species were introduced belonging to the order Perciformes (Cichla sp., Cichla monoculus and Oreochromis niloticus) and 22 are considered possibly endemic to the Middle Eastern Northeast Region. The ictiofauna of the Apodi/Mossoró river follows patterns found in Brazilian rivers, with predominance of Characiformes and Characidae species
Keywords: Ictiofauna; Rio Apodi/Mossoró; Semiárido potiguar.; Região neotropical; Ichthyofauna; River Apodi/Mossoró; Potiguar semi-arid; Neotropical region; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA